2014
DOI: 10.1590/0004-282x20130250
|View full text |Cite
|
Sign up to set email alerts
|

Ability of aphasic individuals to perform numerical processing and calculation tasks

Abstract: Objective: To compare performance on EC301 battery calculation task between aphasic subjects and normal controls of the same sex, age, and education. Method: Thirty-two aphasic patients who had suffered a single left hemisphere stroke were evaluated. Forty-four healthy volunteers were also selected. All subjects underwent a comprehensive arithmetic battery to assess their numerical and calculation skills. Performances on numerical processing and calculation tasks were then analyzed. Results: Aphasic individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…We observed that aphasic individuals showed changes in numerical processing and calculation tasks that were not observed in the healthy population. Although the groups were different according to age and gender, we do not believe that this difference interfered with the results, since there were no elderly subjects in our sample and there is no evidence of cognitive changes in adults [20]. As far as gender is concerned, there is a report of a little advantage of males [4] but in most studies, including one that was done with the EC 301 battery, no statistically significant difference between the performance of males and females was found [21] [22], Table 1.…”
Section: Discussionmentioning
confidence: 76%
“…We observed that aphasic individuals showed changes in numerical processing and calculation tasks that were not observed in the healthy population. Although the groups were different according to age and gender, we do not believe that this difference interfered with the results, since there were no elderly subjects in our sample and there is no evidence of cognitive changes in adults [20]. As far as gender is concerned, there is a report of a little advantage of males [4] but in most studies, including one that was done with the EC 301 battery, no statistically significant difference between the performance of males and females was found [21] [22], Table 1.…”
Section: Discussionmentioning
confidence: 76%
“…The low performance of the patients in the serial writing task, in which patients should write alphabet and number sequences from 1 to 21, may have been due to failure in lexical access to the information in question. This difficulty might be attributable to a lexical-semantic disorder that also underlies language impairments and their relationships with numerical processing 31 . Alternatively, it might be attributable to memory deficit, where such that recall of the items in sequence is necessary in order to subsequently reproduce them.…”
Section: Discussionmentioning
confidence: 99%